A Consortium of Rhizosphere-Competent Actinobacteria Exhibiting Multiple Plant Growth-Promoting Traits Improves the Growth of Avicennia marina in the United Arab Emirates - El-Tarabily, Khaled A.; Sham, Arjun; Elbadawi, Alaa A.; Hassan, Amira H.; Alhosani, Bashaer K. K.; El-Esawi, Mohamed A.; AlKhajeh, Abdulmajeed S.; AbuQamar, Synan F. (Frontiers in Marine Science, 2021)
Gray mangrove (Avicennia marina) is the dominant vegetation distributed along the coast of the United Arab Emirates (UAE). Despite its performance as natural coastal guardians, very little is known about the reforestation projects to increase mangrove cover over the years in the UAE and in the Arabian Gulf. Plant growth-promoting actinobacteria (PGPA) were isolated from the mangrove rhizosphere sediments found in the UAE and were evaluated for their potential to produce plant growth regulators (PGRs) and to enhance mangrove growth under seawater irrigation conditions. In vitro screening identified nine rhizosphere-competent actinobacterial isolates, in a naturally competitive environment, of which Streptomyces coelicoflavus (Sc) showed a high phosphorus solubilizing activity. Moreover, Streptomyces polychromogenes (Sp), Streptomyces bacillaris (Sb), and Streptomyces ferrugineus (Sf) produced auxins, polyamines (PAs), and 1-aminocyclopropane-1-carboxylic acid (ACC) deaminase, respectively. Although sediment inoculation with single isolates significantly improved the dry biomass of mangrove shoots (43.2–74.0%) and roots (40.8–75.9%), the consortium of isolates (Sc/Sp/Sb/Sf) caused a greater increase in the dry weight of shoots (82.1%) and roots (81.6%) compared with seawater-irrigated plants (control). In our greenhouse experiments, the levels of photosynthetic pigments, in planta auxins, and PAs significantly increased in plant tissues inoculated with Sc/Sp/Sb/Sf; whereas ACC contents were reduced. This was also evident as the maximum velocity of rubisco carboxylation (Vcmax) increased four-fold in plants treated with the mixture of isolates over control. To the best of our knowledge, this is the first study reporting culturable halotolerant, rhizosphere-competent PGPA inhabiting salty and arid ecosystems applied individually or in combination to promote mangrove growth under harsh conditions such as those found in the Arabian coastal areas.